Innovative Instruments of Monetary and Fiscal Policy - Danylyshyn, D.; Dubyna, M.; Zabashtanskyi, M.; Ostrovska, N.; Blishchuk, K.; Kozak, I. (Universal Journal of Accounting and Finance, 2021)
Any economic system can be identified as cyclical fluctuations: ups and downs in the economy, which are caused by shocks of aggregate demand and aggregate supply and called business cycles, economic or business cycles. The phases of business cycles are the rise, "peak", recession (or decline) and "bottom", i.e. the crisis. Often such fluctuations in business activity are unpredictable and irregular. At the present stage of development, the state of Ukraine is unstable and characterized by significant crisis processes and phenomena, including critical growth of debt, devaluation of the national currency and limited reserves of the National Bank, reduced lending by banks to the real sector, low financial stability and more. These challenges are exacerbated by the impact of modern global external factors destabilizing financial systems at various levels and financial and economic relations, including the COVID-19 pandemic, which raises the issue of justifying the development and implementation of effective innovative monetary and fiscal policy instruments. The authors explored the nature, components and objectives of monetary and fiscal policy. The authors analyzed the challenges of stabilizing the monetary sector and fiscal policy and developed improving tools. The authors proposed an algorithm for assessing the effectiveness of the monetary policy, where the main criteria for the effectiveness of monetary policy are the criteria that contribute to macroeconomic stability. Regarding innovative fiscal policy instruments, the authors proposed to provide targeted support for industries or projects, namely, the algorithm for determining targeted support for sectors, which implies the creation of clusters of industries and considers the possible negative consequences of the COVID-19 pandemic. The proposed instruments will allow stabilizing the economy to a greater extent, as well as to ensuring more excellent price stability, maintaining a stable exchange rate and promoting balanced economic growth.
Keywords: Cluster, Economic Cyclical Fluctuations, Financial Relations, Fiscal Instruments, Fiscal Policy, Monetary Policy.